Analysis of Direct Interaction between Viral DNA-binding Proteins by Protein Pull-down Co-immunoprecipitation Assay - Lechuga, Ana (Bio Protoc, 2018)
This protocol analyzes the direct interaction between two DNA-binding proteins by pull-down co-immunoprecipitation. One of the proteins is overexpressed in E. coli as HA-tagged recombinant protein and cell-free extracts are immunoprecipitated in HA-affinity resin. Cell extracts are treated with nuclease to degrade DNA and RNA, which rules out nucleic acid-mediated indirect interaction. Then, a second immunoprecipitation step is performed using the purified putative partner protein. Co-immunoprecipitated proteins can be detected either by Coomassie Blue staining and/or Western blotting (WB) if a specific antibody is available. Moreover, many DNA/RNA binding proteins are highly electropositive, which can hinder WB under standard conditions, as has been shown in histones and histone-like proteins. In this case, we show that the high isoelectric point of the putative partner results in a poor transfer. Tips to troubleshot WB transfer of highly electropositive DNA-binding proteins are provided.